Mathematics at National Pedagogical Institute: subjects and teachers - Banionis, Juozas (Lietuvos matematikos rinkinys, 2015)
The article deals with the development of the subjects of mathematics and the teachers who taught them at National Pedagogical Institute in 1935–1943. National Pedagogical Institute was initially established in Klaipėda in 1935, moved to Panevėžys in 1939 and in the same year finally established in Vilnius. Alongside with the teachers M. Mačernis, P. Naujokaitis, M. Krikščiūnas who devoted many years to teaching there were well known mathematicians O.E. Stanaitis and G. Žilinskas. In 1935–1943, methodology of calculus and geometry gained the grounds, and content of mathematics developed from elementary mathematics to high mathematics.